Empirical analysis of the environmental Kuznets curve for economic growth and CO2 emissions in North African countries - Touitou, Mahommed (Empiryczna analiza środowiskowej krzywej Kuznetsa dla wzrostu gospodarczego i emisji CO2 w krajach Afryki Północnej, 2021)
This study aimed at examining the relation between economic growth and carbon dioxide (CO2) emissions in North African countries in the period 2000-2018. To prove this, the author applied the OLS method of the two variables describing the Environmental Kuznets Curve: GDP per capita and CO2. The results show that GDP per capita reflects the influence of changes in the level of income on environmental pollution in five of the seven countries surveyed
Econometrics = Ekonometria, 2021, Vol. 25, No. 2, s. 67-77
Keywords: CO2 emissions; economic growth; environment; panel cointegration approach; emisja CO₂; wzrost gospodarczy; środowisko; podejście kointegracji paneli